Penguatan Kenyamanan dan Kesejahteraan Kampus melalui Gotong Royong Kebersihan - Sirojuddin Abror; Muhammad Na’im Idris; Novritsar Hasitongan Pakpahan; Pratolo Saktiawan; Adi Herisasono (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Cleanliness and comfort of the campus environment are crucial factors in supporting the quality of learning, well-being, and social interaction of the academic community. This community service project aims to analyze the implementation of community service programs for cleanliness and its impact on campus comfort and well-being using the Participatory Action Research (PAR) method. This method actively involves students, lecturers, and staff in the planning, implementation, and evaluation of activities, thereby fostering a sense of responsibility, concern, and ownership of the campus environment. Activities included cleaning classrooms, courtyards, gardens, and public facilities, as well as the collection of organic and non-organic waste. The results of the community service project confirm that the community service program for campus cleanliness not only transformed the campus environment from its previous condition but also raised awareness among the academic community about maintaining a clean environment and could become a weekly campus activity. This project confirms that participatory activities such as community service programs can be an effective strategy in creating a clean, comfortable, healthy, and harmonious campus in a sustainable manner.